COMPARATIVE DISCOURSE STUDIES IN LINGUISTICS - Kholboboeva Aziza Sherboboevna (Journals Park Publishing, 2022)
Discourse is sometimes considered another level of the language, or at least another level of language analysis. This article discusses the issue of “comparative discourse ” as linguistic phenomen.
Keywords: methodological formation, written mode of discourse, intertextual, minimum units, macrostructure